2016
DOI: 10.3892/ijo.2016.3736
|View full text |Cite
|
Sign up to set email alerts
|

MEK inhibitors against MET-amplified non-small cell lung cancer

Abstract: Several receptor tyrosine kinases (RTKs) including EGFR, ALK, and MET have been identified as therapeutic targets in non-small cell lung cancer (NSCLC). Among the downstream pathways of RTKs, the MAPK pathway is particularly important for cancer cell proliferation, differentiation, and survival. In this study, the effects of MEK inhibitors (trametinib and PD0325901) in several NSCLC cell lines with driver gene alterations, especially RTK genes, were tested in vitro using an MTT assay, and a wide range of sensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…In addition, Western Blot analysis revealed that pretreatment with LY294002 abolished the IL‐17A induced up‐regulation of PI3K and AKT either total protein levels or phosphorylated protein levels respectively (* P < 0.05, ** P < 0.01) (Figure C and D). These results were similar to the results from previous studies using the same inhibitor . Taken together, the results demonstrated that the IL‐17A promoted GBM cell migration and invasion were dependent on MMP‐2/9 and Twist via activating PI3K/AKT signalling pathway.…”
Section: Resultssupporting
confidence: 90%
“…In addition, Western Blot analysis revealed that pretreatment with LY294002 abolished the IL‐17A induced up‐regulation of PI3K and AKT either total protein levels or phosphorylated protein levels respectively (* P < 0.05, ** P < 0.01) (Figure C and D). These results were similar to the results from previous studies using the same inhibitor . Taken together, the results demonstrated that the IL‐17A promoted GBM cell migration and invasion were dependent on MMP‐2/9 and Twist via activating PI3K/AKT signalling pathway.…”
Section: Resultssupporting
confidence: 90%
“…Treatment with trametinib alone decreased the growth of all cell lines with EGFR mutation alone or with a BRAF fusion; cell lines with the BRAF fusion were more sensitive, which is consistent with published data showing only limited activity of MEK inhibitors in EGFR-mutated cell lines. 20 Indeed, we found that a maximum inhibition of cell growth of only 50% was achieved by trametinib (results not shown). This may indicate that a subpopulation of cells from lines expressing a BRAF fusion can still survive after MEK inhibition.…”
Section: Combined Inhibition Of Mek and Egfr As Potentialmentioning
confidence: 86%
“…However, another trial targeting Asian patients with EGFR-WT non-squamous NSCLC was prematurely terminated due to the increased incidence of interstitial lung disease in patient group treated with erlotinib and tivantinib, although preliminary data revealed that the PFS was longer in that group [ 20 ]. Met amplification is an excellent predictor of sensitivity to Met inhibitors such as PHA-665752 and crizotinib [ 22 , 23 ]. Impaired Met degradation mediated by Met exon 14 mutations has also been documented in NSCLC [ 24 26 ].…”
Section: Discussionmentioning
confidence: 99%